Laura Letinsky : petits écarts affectueux - Jean, Marie-Josée (CV Photo)

(untitled) (Les Productions Ciel variable, 1999)
Summary The author examines the expression and the modalities of communicating affection in a selection of Laura Letinsky's works in which the complexity of the love relationships between men and women is presented. Letinsky's images depict couples before or after making love, capturing moments when the women are emotionally distant. The attitude of many female characters - the nonchalance of some, the absent air of others - manifests their individuality in the gap that they impose between themselves and the other. This distant attitude negates the submissive position in which erotic imagery has most frequently portrayed women. As well, the gap produced by the distance of certain female characters opens up an indispensable space within which lies the proof that they have an effect on the other. Affection then arises as a need to close this gap.